THE ANIMATED PSYCHE: ANALYZING INSIDE OUT 2 (2024) THROUGH FREUDIAN PSYCHOANALYSIS - Rachmandani, Andika (Universitas Negeri Surabaya, 2025)
This research analyzes Inside Out 2 (2024), directed by Kelsey Mann and produced by Pixar, through Sigmund Freud’s psychoanalytic concepts of the Id, Ego, and Superego. Focusing on Riley’s emotional journey through adolescence, the film explores how it conveys complex psychological ideas through animation. Using a Freudian lens, the study examines narrative elements, character dynamics, and emotional interactions. While previous research has explored symbolism and emotional expression in the film, few studies have directly linked them to Freudian theory. This study fills that gap by analyzing selected scenes and character relationships through a psychoanalytic literary lens. By viewing emotions like Joy and Anxiety as representations of the mind’s structure, the thesis argues that the film effectively adapts Freudian theory for modern audiences. Ultimately, it contributes to discussions on the intersection of psychology, media, highlighting the film's value in illustrating emotional and cognitive development.